Asean-Republic of Korea digital partnership: The imperatives of trans-regional cooperation in controlling Covid-19 - Hartono, Anthony Setiawan; Phuong, Nguyen Thao; Perwita, Anak Agung Banyu (Universiti Utara Malaysia Press, 2021)
As the raging pandemic of COVID 19 continues to spread and bring the world to its knees, governments are struggled searching for effective solutions to prevent the further expansion of the disease and its tremendous impact to the human’s life, specifically economy. Yet, the Republic of South Korea (ROK) has successfully responded to such problems with the advanced technology. In the contrary, ASEAN countries are still struggling to manage the massive impacts of COVID-19 due to its lack of equal technological access. Hence, this essay will not only explore the lesson and learned of Korea for ASEAN and ASEAN existing conditions but also outlines the possible adoptions of ASEAN-Korea Digital Partnership in the post-COVID 19. After being amalgamated in extensive and strategic relations for more than 30 years, ASEAN and ROK has accomplished outstanding achievements and blossoming development in partnership. Specifically, technological cooperation has always been the heart of ASEAN-ROK relations in which furnish the technological advancements for ASEAN and open up to Korea an ideal market for its technological production. On those grounds, ASEAN-Korea Digital Partnership is more than feasible to be pursued. However, there are several challenges that intercept such as ASEAN economy, technological, and political incompatibilities. Therefore, the Digital Partnership needs some adjustments which can be deciphered as follows: 5G interconnectivity, surveillance system, e-commerce, and cybersecurity cooperation. By formulating cooperation in such areas which are supported by the aforementioned data, this essay can be taken into account for the discussions of the near-future ASEAN-Korea Digital Partnership’s operation.